Tongan Crip Gang: A Tongan American Identity - Hafoka, ‘Esiteli (Art/Research International, 2024)
This article is an articulation of Tongan angafakafonua (way of the land, culture)as Tongan identity and its (re)makings through religion and gangs in the United States. Based on a section of my doctoral thesis, I examine the influence of the Mormon Church on Racketeer Influenced and Corrupt Organizations (RICO) Act charges.1 This article acknowledges that legislators, driven by their Mormon religio-racial ideology, interpreted the legislation in an exclusive manner. They took liberties to explicitly exclude first-generation Tongan Americans based on their preference for street gangs rather than the fraternal organizations associated with the Church. During the period between the settlement of Utah and the RICO trial of Siale Angilau, American-born Tongans of the first generation modified angafakafonua to address the needs of a growing Tongan community in the United States. In the later years of this transitional period, second-Generation Tongan Americans utilized angafakafonua to counteract excessive surveillance by gang task forces, racial profiling, and discriminatory practices employed by the state.